2021
DOI: 10.1080/22423982.2021.1961392
|View full text |Cite
|
Sign up to set email alerts
|

Access to ultrasound imaging: A qualitative study in two northern, remote, Indigenous communities in Canada

Abstract: Ultrasound imaging is an essential component of healthcare services. This study sought to explore perceptions of access, and factors which shape access, to ultrasound imaging in two northern, remote, Indigenous communities in Canada. Using interpretive description as a methodological approach and a multi-dimensional conceptualisation of access to care as a theoretical framework, 15 semi-structured interviews were conducted in the northern Canadian communities of Stony Rapids and Black Lake, Saskatchewan. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…However, the use of 5G-based robot-assisted remote ultrasound system in persons with disabilities decreases the total process time, as compared with routine ultrasound. In particular, patients from remote areas take a longer time to arrive at medical facilities and undergo an ultrasound examination ( 29 ). This study suggests that the 5G-based robot-assisted remote ultrasound system will hopefully provide patients at rural care centers with the same diagnostic possibilities as those at tertiary hospitals where experts are instantly available.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of 5G-based robot-assisted remote ultrasound system in persons with disabilities decreases the total process time, as compared with routine ultrasound. In particular, patients from remote areas take a longer time to arrive at medical facilities and undergo an ultrasound examination ( 29 ). This study suggests that the 5G-based robot-assisted remote ultrasound system will hopefully provide patients at rural care centers with the same diagnostic possibilities as those at tertiary hospitals where experts are instantly available.…”
Section: Discussionmentioning
confidence: 99%
“…Lower rates of non-obstetrical ultrasound utilization in many remote areas of the province may reflect barriers which patients face in accessing ultrasound, such as the need to travel far distances-sometimes by plane-to reach an ultrasound facility. 2 However, it is interesting that utilization rates did not continue to decrease with higher levels of geographic remoteness, but were lowest in mid-geographically remote areas. 14 This may be explained by ultrasound and radiography being the most accessible imaging modalities in many rural and remote areas, leading physicians to order ultrasound imaging even in cases where another imaging modality may be more appropriate.…”
Section: Discussionmentioning
confidence: 96%
“…1 Despite its importance in clinical care, ultrasound is not available in many rural and remote communities in Canada and around the world, creating inequities in access to this important imaging modality. 2 While disparities in access to ultrasound imaging among specific sociodemographic groups-including individuals in rural and remote communities-have been reported, 2 it is less clear how disparities in access to ultrasound imaging impact utilization of non-obstetrical ultrasound imaging. One of the most frequently cited theoretical models of healthcare utilization, first described by Andersen in 1968, proposes that healthcare utilization can be predicted by an individuals' predisposition to use services, factors which enable or impede use, and individuals' perceived and evaluated need for care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In other communities where an itinerant sonographer visits the community on a monthly basis, long wait times often result. 4 Telerobotic ultrasound is a new technology which equips a sonographer or radiologist with the ability to remotely manipulate an ultrasound probe, control all ultrasound machine settings, and remotely perform an ultrasound exam (Figure 1). 5 Clinical trials which have demonstrated the feasibility of a telerobotic approach for performing abdominal and obstetrical ultrasound imaging 6,7 and recent commercialization of telerobotic ultrasound systems [8][9][10] have paved the way for the implementation of this technology in remote communities.…”
Section: Introductionmentioning
confidence: 99%